3
$\begingroup$

The differential equation is as follows-

$$\frac{d^2 x}{dt^2} + 5 \frac{dx}{dt} + 6x = e^t $$

I use laplace transform to make it to become - $$X(s) = \frac{1}{(s-1)(s+3)(s+2)}$$ where $X(s)$ is the Laplace transform of $X(t)$

So now I am trying to find $X(t)$ using inverse transform.

From partial fractions-

$X(s) = \frac{1}{(s-1)(s+3)(s+2)} = \frac{A}{s-1} + \frac{B}{s+3} + \frac{C}{s+2} $

Numerator - $ 1 = A(s+3)(s+2) + B(s-1)(s+2) + C(s-1)(s+3) $

I am stuck from here on how to carry on this partial fraction

Can I sub all s values to be 0 ?

For example

$1 = A(0+3)(0+2)$

$1= B(0-1)(0+2) $

$1 = C (0-1)(0+3) $

$\endgroup$
1
  • 1
    $\begingroup$ You can expand everything, and compare the coefficients of $s^2$,$s$,$1$ on both sides. Or you can even substitute some values for $s$. $\endgroup$
    – Botond
    Jul 22, 2018 at 21:02

3 Answers 3

3
$\begingroup$

$ s=0$ is not the best choice

There are three values to assign to $s$ which makes our life very easy.

$$1 = A(s+3)(s+2) + B(s-1)(s+2) + C(s-1)(s+3)$$

$$ s=1 \implies 12A=1 \implies A=\frac {1}{12}$$

$$ s=-3 \implies 4B=1 \implies B=\frac {1}{4}$$

$$ s=-2 \implies -3C=1 \implies C=\frac {-1}{3}$$

Now you proceed with the inverse Laplace Transform.

$\endgroup$
5
  • $\begingroup$ For example , why can’t I use -4 to find B ? Apparently I will get B= 1/10 which is different if I use -3. is this ok? $\endgroup$
    – user185692
    Jul 22, 2018 at 21:34
  • $\begingroup$ Or must I only identify -3 and use -3 ? $\endgroup$
    – user185692
    Jul 22, 2018 at 21:35
  • $\begingroup$ @user185692 If you use -4 then you will have $1=A(-4+3)(-4+2)+B(-4−1)(-4+2)+C(-4−1)(-4+3)$ which does not give you a simple solution for $B$. As you see $ A$ and $C$ are still present. $\endgroup$ Jul 22, 2018 at 21:39
  • $\begingroup$ Why must I sub all the s values to be -4 whereas you sub 1,-3,-2 for A,B, and C respectively ? I was asking must these 3 numbers be fixed to be 1,-3,-2 ? Like for example, could I use 1,-4,-2 respectively for A, B, C. Thanks!!! $\endgroup$
    – user185692
    Jul 22, 2018 at 21:48
  • $\begingroup$ @user185692 When you let $s=1$ the coefficients of $B$ and $C$ become $0$. The only survivor is $A$. $\endgroup$ Jul 22, 2018 at 21:51
2
$\begingroup$

So, if we have that $$1 = A(s+3)(s+2) + B(s-1)(s+2) + C(s-1)(s+3)$$ We can expand everything to get $$1=A(s^2+5s+6)+B(s^2+s-2)+C(s^2+2s-3)$$ $$1=s^2(A+B+C)+s(5A+B+2C)+1(6A-2B-3C)$$ So we must have that $A+B+C=0$, $5A+B+2C=0$ and $6A-2B-3C=1$.

Or alternatively: $$1 = A(s+3)(s+2) + B(s-1)(s+2) + C(s-1)(s+3)$$ If we substitute $s=1$ we get that $$1=A(1+3)(1+2)$$ With $s=-2$ we get that $$1=C(-2-1)(-2+3)$$ And with $s=-3$ we get that $$1=B(-3-1)(-3+2)$$

And here is a video about the partial fraction decomposition, you might find it helpful.

$\endgroup$
6
  • $\begingroup$ how do you know what coefficients to put into A , B and C for the “A+B+C” , “5A+B+2C” , “6A-2B-3C” ? $\endgroup$
    – user185692
    Jul 22, 2018 at 22:02
  • $\begingroup$ @user185692 What do you mean? Would you like to ask the way I've got the 3 equation or the way you can solve it? $\endgroup$
    – Botond
    Jul 22, 2018 at 22:04
  • $\begingroup$ The way you have gotten the 3 equations. $\endgroup$
    – user185692
    Jul 22, 2018 at 22:07
  • $\begingroup$ @user185692 So, after expanding everything, we get that $1=A(s^2+5s+6)+B(s^2+s-2)+C(s^2+2s-3)$. Now we want to make the right-hand side nicer, to look like a "normal" polynomial, something like the $ax^2+bx+c$. And if I didn't mess it up, we get that $1=s^2(A+B+C)+s(5A+B+2C)+1(6A-2B-3C)$. The $2$ sides look really different, right? But they should be equal for every $s$! So how can it be? If the right-hand side looks exactly like the left-hand side. So, how many $s^2$ do we have on the right? $A+B+C$. And on the left? $0$. So they should be equal: $A+B+C=0$, and so on. Is it clear now? $\endgroup$
    – Botond
    Jul 22, 2018 at 22:11
  • $\begingroup$ Yes!! Thanks a lot .. $\endgroup$
    – user185692
    Jul 22, 2018 at 22:32
1
$\begingroup$

$$X(s) = \frac{1}{(s-1)(s+3)(s+2)}$$ Substitute $k=s+2$ $$F(k) = \frac{1}{(k-3)(k+1)k}$$

$$F(k) = \frac{1}{(k-3)}\left(\frac 1 {(k+1)k} \right)$$ $$F(k) = \frac{1}{(k-3)}\left(\frac 1 k-\frac 1 {k+1} \right)$$ $$F(k) = \frac{1}{(k-3)}\frac 1 k-\frac{1}{(k-3)}\frac 1 {(k+1)} $$ $$F(k) = \frac 13 \left (\frac{1}{(k-3)}-\frac 1 k\right )-\frac 14\left(\frac{1}{(k-3)}-\frac 1 {(k+1)} \right )$$ $$F(k) = \frac 1 {12} \frac{1}{(k-3)}-\frac 1{3k}+\frac 14\frac 1 {(k+1)} $$ Substitute back $k=s+2$ $$X(s)=-\frac 1{3(s+2)}+\frac 1{4(s+3)}+\frac 1 {12(s-1)}$$ $$x(t)=-\frac 1{3}e^{-2t}+\frac 1{4}e^{-3t}+\frac 1 {12}e^{t}$$ It's a bit longer but i find this method easier

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.